Regeneración natural de especies forestales en un bosque secundario del CIEFOR Puerto Almendra, Loreto, Perú, 2022 - Flores Rios, Chalo Frankcois (2025)
The objective of this study was to evaluate the natural regeneration of a secondary forest of CIEFOR – Puerto Almendra. 20 structural plots of 10m x 10m, 5m x 5m and 2m x 2m were installed, where the stems, latizales and Brinzales were evaluated, respectively. The floristic composition was represented by a total of 388 individuals, grouped into 68 identified species, 53 genera and 29 botanical families. In the Brinzal category, the species with the highest ecological weight were B. utile with 67.4%, I. quaternata with 54.14% and P. tomentosa with 14.82%. In the Latizal category were P. tomentosa (34.91%), P. divaricatum (23.36%) and E. albiflora (18.54%); and in the stem category they were P. tomentosa (30.46%), P. igneiflora (18.84%), T. guianensis (18.08%). The conclusion is that there are plant species that help to regenerate a secondary forest in a natural way.